Laparoscopic Approach in Correction of Adult Diaphragmatic Morgagni Hernia - Mazni, Yarman; Prabowo, Andrio W (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Adult diaphragmatic hernia of Morgagni is a very rare congenital anomaly. Therefore, to date there is no standard surgical techniques used in the management. Thus, a systematic review aimed to find the highest evidence in the management. Method. A systematic review conducted in accordance with PRISMA. Literature search proceeded on PubMed and ScienceDirect using keywords "diaphragmatic hernia of Morgagni in adult", and "treatment". These articles were reviewed and appraised for the study design used, enrolled samples, validation of results, etc. to find out the level of evidence. The analysis was focused on length of stay, the recurrence, and complications. Results. There were 15 articles reviewed. The transabdominal approach provides better exposure, short length of stays, and low complications. Laparoscopic has been used widely and replaces open surgery. The defect closure using mesh is indicated in large defect of ≥20 cm2 . The hernial sac is unnecessary to resect, with no complication such as seroma or recurrence. Conclusion. A laparoscopic approach referred to the method of choice in the management of adult diaphragmatic hernia of Morgagni. Unnecessary resection of hernial sac and tension free defect closure should be of one consideration.